Epidemiological Profile of Vulvar Carcinoma in Nepalese Women Managed at Bhaktapur Cancer Hospital - Shresha, Eliza; Bista, Kumar Bahadur; Siddiqui, Saharoj (Nepalese Journal of Cancer, 2025)
Introduction: This study aims to analyze the epidemiological risk factors and management outcomes of vulvar cancer in histologically confirmed cases based on tumor stage. Vulvar cancer is an uncommon form of cancer and presents a public health issue comparable to other types of malignancies. Cost associated with diagnosis, medical treatment, and psychological well-being of female.Methods: This was a hospital-based retrospective descriptive study conducted over one month. Women with diagnosed case of vulvar carcinoma between 2021 to 2023 who were undergoing treatment at Bhaktapur Cancer Hospital in the Department of Gynecologic Oncology were included in this study. The risk factors, symptoms, stage, histological type, and treatment were recorded. The categorical variables obtained were summarized using frequency and percentage.Results: total of 25 patients with biopsy confirmed vulvar malignancy were included in the study. The majority of the patients were postmenopausal, with ages exceeding 50 years, accounting for 18 (72%) cases, and were multiparous. Squamous cell carcinoma constituted 18 (72%) cases of the total histological types and was most common histological variant. The most frequently performed procedure was radical vulvectomy combined with bilateral pelvic lymphadenectomy which accounted for 14 (56%) of totalprocedure.Conclusion: Vulvar carcinoma is a rare type of gynaecological malignancy in Nepal, and mainly affects women in their postmenopausal stage. The commonest type is the squamous cell carcinoma that is usually diagnosed in early cases. Risk factors were commonly parity and smoking. The primary therapy was surgery, particularly radical vulvectomy and lymphadenectomy.